CROSSROADS OF FAITH: ADAPTATION OF LOCAL RELIGIOUS TRADITIONS IN THE FLOW OF GLOBALISATION - Sigit Sugiardi; Aslan Aslan (Adisam Publisher, 2025)
This study aims to examine the forms of adaptation of local religious traditions in the face of globalisation and its impact on the cultural and religious identity of the community. Using a literature review method, this study analyses various literature discussing the dynamics of change, influencing factors, and strategies for preserving religious traditions amid the challenges of modernisation and globalisation. The results of the study indicate that the adaptation of local religious traditions is carried out through ritual modifications, the use of digital technology, innovations in presentation, and the integration of more universal religious values. This adaptation process is influenced by factors such as education, media, cultural interaction, the role of the younger generation, and government policy support. Although there is a risk of shifting meanings and authenticity of traditions, adaptation carried out wisely and participatively has proven to be able to preserve traditions while strengthening the cultural and spiritual identity of the community. This study recommends the importance of cross-sector collaboration and the involvement of the younger generation in efforts to preserve local religious traditions so that they remain relevant and contribute positively in the era of globalisation.